SEISMOGENIC NODES DEFINED BY PATTERN RECOGNITION IN THE CENTRAL PART OF THE ALPINEHIMALAYAN BELT - Novikova, O.; Gorshkov, A. (Bulletin of the Geological Society of Greece, 2016)
Information on the areas prone to the strongest earthquakes in a region is very important for knowledgeable seismic hazard and risk assessment. We consider the central part of the Alpine-Himalayan Belt (Caucasus–Kopet Dagh-Alburz) for the recognition of seismogenic nodes capable of M7+ earthquakes. The nodes formed around the intersections of the fault zones are viewed as objects of recognition which have been described by the common set of geologic, geomorphologic and geophysical parameters. 150 nodes out of 510 ones delineated in the Caucasus Kopet Dagh- Alburz region were recognized prone for earthquakes M7+. We have recognized a number of capable nodes where earthquakes M7+ have not yet been recorded.